2019
DOI: 10.1038/s41598-019-55034-9
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization and printability of Sodium alginate -Gelatin hydrogel for bioprinting NSCLC co-culture

Abstract: 3D bioprinting improves orientation of in vitro tumor models by offering layer by layer positioning of cancer cells and cancer associated fibroblasts (CAFs) which can replicate tumor microenvironment. Aim of this study was to develop a sodium alginate -gelatin (SA-GL) hydrogel by optimizing rheological parameters to print non-small cell lung cancer (NSCLC) patient derived xenograft (PDX) cells and lung CAFs co-cultures. SA-GL hydrogels were prepared, and rheological properties were evaluated. Both the cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 67 publications
2
98
0
Order By: Relevance
“…Due to its rapid shear recovering property, our vitroGel hydrogel system can maintain the printing structure without any smearing problems through immediate curing process. However, optimal stiffness and stability of printed cell laden scaffolds, depend upon the cross-linking methods and elasticity nature of the bioinks 36,62 . Crosslinker concentration and crosslinking time determine the viscosity of the hydrogel system 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its rapid shear recovering property, our vitroGel hydrogel system can maintain the printing structure without any smearing problems through immediate curing process. However, optimal stiffness and stability of printed cell laden scaffolds, depend upon the cross-linking methods and elasticity nature of the bioinks 36,62 . Crosslinker concentration and crosslinking time determine the viscosity of the hydrogel system 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…The bioprinting process, as shown in Figure 1B, consists of the prior bioprinting phase, where alginate/gelatin bioinks were synthesized and suitable cells were selected. The alginate/gelatin bioinks were produced in different concentrations, based on the cell line used, the printability and the cell viability reported on previous studies (Mondal et al, 2019;Chawla et al, 2020). Next, after cells were cultured in 2D conditions until confluency, they were mixed with the appropriate bioink and were bioprinted according to the gcode instructions, generating the 3D culture design shown in Figure 1B.…”
Section: Bioprinter Assembly and Bioprinting Processmentioning
confidence: 99%
“…Following the bioprinter's calibration, we synthesized bioinks based on low cost polymer precursors (alginate, gelatin). As shown in Figures 2, 3, these natural polymers, when combined, apart from their known biocompatibility, possess special crosslinking and rheological properties (Mondal et al, 2019 ; Figures 2, 3). Prior to bioprinting, cells were first mixed into the syringe with warmed (37 • C) bioink solution, which lowers the viscosity and thus allows cells to mix efficiently, as shown by the oscillatory temperature ramp of A1.8 G3 and A2 G3 in Figures 3A,C. In addition, these bioinks were found within the printability window (tanδ = 0.25-0.45, (Gao et al, 2018) as observed in Figure 3D, with tanδ = 0.32 at 1 Hz.…”
Section: Cell Survival and Proliferation After The Bioprinting Processmentioning
confidence: 99%
“…To address these issues, 3D cell culture models are a reliable alternative, providing experimentally accessible human models to study the biological processes of cancer. Several 3D culture platforms such as spheroids, organoids, hydrogels, 3D scaffolds, 3D bio-printing, and microfluidics have attempted the recreation of certain aspects of tumor microenvironments present in tissues including the brain [30][31][32][33][34][35][36], breast [37][38][39][40][41][42][43], ovarian [44][45][46][47][48][49][50][51], bone [52][53][54][55][56][57][58], liver [59][60][61][62][63][64][65], lung [66][67][68][69][70][71][72], colon [73][74][75][76]…”
Section: Mimicking Tme In Three-dimensionsmentioning
confidence: 99%